The moderating effect of team psychological empowerment on the relationship between abusive supervision and engagement. Issue 1 (11th February 2019) - Kirrane, Melrona; Kilroy, Steven; O'Connor, Clíodhna
Abstract : Purpose: Managers exert considerable effort to foster employee engagement given its positive organisational consequences. However abusive supervision, not uncommon in the organisational context, is said to damage hard-won gains in this arena. The purpose of this paper is to explore how the deleterious effects of abusive supervision on engagement can be attenuated. Specifically, the paper examines the moderating role of team psychological empowerment (TPE) in the negative relationship between abusive supervision and engagement. Design/methodology/approach: The paper employs survey data from a diverse sample of 191 employees. Findings: Abusive supervision is negatively associated with employee engagement. TPE moderates the negative relationship between abusive supervision and engagement (vigour and dedication components). Research limitations/implications: The use of self-report measures in this cross-sectional study limits the generalisability of the findings and inferences of causality. Future studies should replicate this investigation among intact teams. Practical implications: Interventions designed to build team effective team dynamics are accessible and fruitful approaches managers can use to counteract the destructive effects of abusive supervision. Originality/value: Managers need to have multiple routes to address the challenges raised by prevalent abusive supervision. The study highlights that working to enhance team dynamics is a cogent strategy to deal with this destructive feature of many organisational contexts.